2023
DOI: 10.1177/10600280231156625
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Data Supporting Use of COVID-19 Vaccinations in the Pediatric Population

Abstract: Objective: The objective of this study was to review the effectiveness and safety of COVID-19 vaccinations in the pediatric population. Data Sources: PubMed/Medline (September 2020 to December 2022), the Centers for Disease Control and Prevention, and Food and Drug Administration (FDA) websites. Study Selection and Data Extraction: Publications regarding the safety and efficacy of COVID-19 vaccinations in children were included. Data Synthesis: Vaccines authorized for use in children include two monovalent mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A study by Stultz et al [54] provided a review of relevant safety considerations regarding COVID-19 vaccines in children, either in authorization studies or post-marketing analyses. These observations confirmed that most common adverse effects are mild/moderate, mostly lasting 1 or 2 days, and typically 16% or less of the time have an impact on the ability to perform daily activities (e.g., school attendance).…”
Section: Surveillance Data (Post-authorization Monitoring)mentioning
confidence: 99%
“…A study by Stultz et al [54] provided a review of relevant safety considerations regarding COVID-19 vaccines in children, either in authorization studies or post-marketing analyses. These observations confirmed that most common adverse effects are mild/moderate, mostly lasting 1 or 2 days, and typically 16% or less of the time have an impact on the ability to perform daily activities (e.g., school attendance).…”
Section: Surveillance Data (Post-authorization Monitoring)mentioning
confidence: 99%